2011
DOI: 10.3758/s13421-011-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation intentions and imagery: individual and combined effects on prospective memory among young adults

Abstract: Prospective memory (PM) has been found to benefit from implementation intentions (i.e., "when I see X, I will do Y"). However, to date, it is unclear whether implementation intentions must incorporate imagery in order to produce a positive effect on PM, or whether the verbal statement alone is sufficient. It is also equivocal whether the use of visual imagery alone improves PM, absent an intentional statement. The present study investigated the individual influences of implementation intentions and imagery, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…The use of implementation intentions, however, could have encouraged most, if not all, high-FL participants to establish a strong associative link, thereby fostering improved PM performance. Recent findings of improved PM performance following implementation intention instruction among undergraduate students (Cohen & Gollwitzer, 2008;Meeks & Marsh, 2010;McDaniel et al, 2008;McFarland & Glisky, 2011) lend additional credence to this argument, as younger adults have been found to possess greater processing resources than older adults (Anderson et al, 1998;Craik & McDowd, 1987). The finding that younger adults can benefit from implementation intentions suggests that although younger adults are capable of developing good plans and making strong associative links, they too may fail to do so at times, and in those cases implementation intentions might encourage engagement in those processes (McDaniel et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…The use of implementation intentions, however, could have encouraged most, if not all, high-FL participants to establish a strong associative link, thereby fostering improved PM performance. Recent findings of improved PM performance following implementation intention instruction among undergraduate students (Cohen & Gollwitzer, 2008;Meeks & Marsh, 2010;McDaniel et al, 2008;McFarland & Glisky, 2011) lend additional credence to this argument, as younger adults have been found to possess greater processing resources than older adults (Anderson et al, 1998;Craik & McDowd, 1987). The finding that younger adults can benefit from implementation intentions suggests that although younger adults are capable of developing good plans and making strong associative links, they too may fail to do so at times, and in those cases implementation intentions might encourage engagement in those processes (McDaniel et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…This hypothesis was supported by Brewer and Marsh (2010), who demonstrated that deeper encoding of the cue-to-context link by way of visualization was associated with better accuracy on event-based PM tasks. Further support for the association between brief visualization exercises utilized during the encoding stage of laboratory PM tasks and enhanced event-based PM has been shown in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012; Altgassen et al, 2015), older adults (Altgassen et al, 2015) individuals with traumatic brain injury (Potvin et al, 2011), and a mixed clinical sample with memory impairments (Grilli & McFarland, 2011). Visualization has also been associated with improvements in time-based PM in young adults (Altgassen et al, 2015), older adults (Altgassen et al, 2015), adult social drinkers (Griffiths et al, 2012), and individuals with moderate-to-severe traumatic brain injury (Potvin et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Several studies report beneficial effects of brief visualization and implementation intentions during encoding for event-based PM (Chasteen et al, 2001; Schnitzpahn & Kliegal 2009; Burkard et al, 2014) and time-based PM (Schnitzpahn & Kliegal 2009) across both healthy (e.g., Meeks & Marsh, 2010) and clinical (e.g., Kardiasmenos et al, 2008) populations. To date, the literature regarding the independent and combined effects of visualization and implementation intentions suggests that the effects of these encoding interventions are not synergistic; that is, using both strategies does not necessarily improve PM performance more than using a single strategy alone (e.g., Meeks & Marsh, 2010; McFarland & Glisky, 2012; cf. McDaniel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, although this indirect relationship between metamemory knowledge, strategy use, and memory performance seems well established when tasks assessing retrospective memory (RM) are used, few studies have examined this relation using tasks that assess prospective memory skills (for recent studies on this topic in adulthood, see Hutchens et al, Running head: Metamemory Knowledge and Prospective Memory 4 2012; McFarland & Glisky, 2012;Rummel & Meiser, 2013). In fact, to our knowledge, no previous study has investigated this specific topic in children.…”
mentioning
confidence: 99%